Adjusting to minimum wage regulation: Evidence from a direct-democracy experiment in Switzerland - Marius Berger; Bruno Lanz (University of Neuchâtel, Institute of Economic Research (IRENE), 2019)
We document firms' adjustment channels to minimum wage regulation, leveraging an unexpected Supreme Court ruling mandating the Swiss canton Neuchâtel to enforce a minimum hourly wage of around CHF20 (approx. USD 20) previously accepted via popular ballot. Given policy discontinuity at cantonal borders, we design a simple two-wave survey of restaurants to measure wages, employment, workers characteristics, and prices, and administer it in Neuchâtel as well as in geographically proximate districts of neighboring cantons. Our data covers pre- and post-enforcement outcomes for 113 restaurants, with information on more than 800 employees distributed over two survey waves. Difference-in-differences estimation on restaurant-level outcomes and on the distribution of wages in our sample indicate small and statistically insignificant impacts on employment and prices, although we find evidence of disemployment effects for restaurants with larger workforce and lower pre-treatment subminimum wages. Worker-level data further suggests that labor-labor substitution is at work, with an increase in the share of less-qualified workers and employment spillovers for workers with wages above the regulatory minimum.
Keywords: J21; J23; J38; C83; R23; 330; Minimum wage regulation; Wage distribution; Workforce composition; Labor-labor substitution; Low-wage jobs; Restaurant industry